Itch intensity in prurigo nodularis is closely related to dermal interleukin‐31, oncostatin M, IL‐31 receptor alpha and oncostatin M receptor beta. Issue 6 (1st February 2021) - Hashimoto, Takashi; Nattkemper, Leigh A.; Kim, Hei Sung; Kursewicz, Christina D.; Fowler, Emilie; Shah, Serena M.; Nanda, Sonali; Fayne, Rachel A.; Paolini, John F.; Romanelli, Paolo; Yosipovitch, Gil
Abstract: Prurigo nodularis (PN) is a chronic skin dermatosis with hyperkeratotic and intensely pruritic nodules. Managing PN‐associated itch is difficult because its aetiology is still unknown. This study aimed to investigate the correlation between itch intensity in PN and the expression of a pruritogenic cytokine interleukin (IL)‐31, its receptor complex components IL‐31 receptor α (IL‐31RA) and oncostatin M receptor β (OSMRβ), and oncostatin M (OSM), which is a ligand of OSMR β, through immunofluorescence staining examination. Itch intensity in PN was closely correlated with the number of dermal IL‐31(+) cells (Spearman's r = 0.551, p < 0.05), dermal IL‐31RA(+) cells ( r = 0.475, p < 0.05) and dermal OSM(+) cells ( r = 0.505, p < 0.05). In addition, the number of dermal OSMRβ (+) cells was increased in PN ( t test, p < 0.05), despite not being correlated with itch intensity (Spearman's r = 0.375, p > 0.05). Major cellular sources of dermal IL‐31 were T cells (27.0% of total IL‐31–expressing cells) and macrophages (35.0%), while those of OSM were mainly T cells (49.8%) and mast cells (26.8%). IL‐31RA–expressing dermal cells were mostly mast cells (49.3%) and macrophages (36.6%), and OSMRβ was mainly expressed by macrophages (51.8%) in the dermis. These findings indicate that IL‐31 (mainly from macrophages and T cells) and OSM (principally from T cells and mast cells) stimulate dermal cells expressing IL‐31RA and OSMRβ (e.g. macrophages), which may further promote itch and inflammation in PN. This complex dermal milieu of cell/cytokine/receptor network can be a therapeutic target for PN‐associated itch.